Legal Politics of Codification of Islamic Marriage Law: A Study of Legal Philosophy and Taqnin Practice in Muslim Countries - Karmawan, Karmawan; Fajar, Abbas Sofwan Matlail; Yunus, Nur Rohim (IBN KHALDUN BOGOR, 2025)
Enshrining Islamic law in writing, particularly in the context of marriage, is a crucial step in transforming fiqh law into positive law in Muslim countries. This codification process reveals not only formal legal efforts but also the evolving nature of legal politics, the direction of state philosophy, and how the state responds to social demands. Islamic marriage law can be codified in various ways, including textual-normative, contextual, and progressive approaches. These differences are due to the ideological, legal, and social conditions of each country. The goal of this study is to examine the connection between legal politics and the codification of Islamic marriage law, investigate the philosophical basis for the practice of taqnin, and compare the methods of codification employed in Muslim countries such as Indonesia, Morocco, Tunisia, and Egypt. This study uses a qualitative, normative, and comparative legal approach, as well as a conceptual, historical, and comparative legal approach. The primary sources of data are official legal documents, including the Compilation of Islamic Law (KHI), Mudawwanah al-Usrah, the Code du Statut Personnel, and the Egyptian Family Law. Secondary sources include books, academic journals, and studies of Islamic legal philosophy. The study's results indicate that legal politics plays a significant role in determining how to codify Islamic marriage law. The state's legal philosophy—whether it is conservative-textual, moderate-contextual, or progressive-normative—has a substantial impact on how it handles taqnin. The principles of maqashid al-shari'ah, such as justice, protection of life, property, and honour, as well as the ability to address the challenges of social pluralism, gender equality, and the legal needs of modern society, are what make codification successful. The results suggest that the future of Islamic law should incorporate a blend of legal philosophy, inter-school dialogue, and interdisciplinary studies. Keywords: Legal Politics; Legal Codification; Islamic Marriage; Muslim State